2019
DOI: 10.1021/acs.jafc.8b06983
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Galloylation Efficacy of Stigmasterol and β-Sitosterol Followed by Evaluation of Cholesterol-Reducing Activity

Abstract: In this study, incorporation of gallic acid into typical phytosterols (β-sitosterol and stigmasterol) through Steglich esterification was optimized employing the protection and deprotection strategy. A novel mechanism leading to side esterification was discovered. Complication of the phenolic hydroxyl groups and side reactions were successfully reduced under the optimized conditions. The structural identity and purity of galloyl stigmasterol and galloyl β-sitosterol were confirmed by NMR, FT-IR, and HPLC-MS. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…The pyrogallol moiety in 2′′-O-galloyl provides additional hydroxyl groups with radical-scavenging and metal-chelating abilities (Fig. 6) [24, 3740].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…The pyrogallol moiety in 2′′-O-galloyl provides additional hydroxyl groups with radical-scavenging and metal-chelating abilities (Fig. 6) [24, 3740].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we screened out nine main active components of semen armeniacae amarum . Among them, stigmasterol performs anti-inflammatory activity, and suppresses airway inflammation by inhibiting allergen-induced immunoglobulin E-mediated responses ( 30 , 31 ). Sitosterol has antioxidant activity ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kaempferol could repair the mesangial cell and ameliorate the renal injury and fibrosis (Zhang et al 2019b;Sharma et al 2020). Beta-sitosterol in Imperatae Rhizoma, Hedyotis Diffusae Herba, and Tripterygii Radixand, and stigmasterol in Coicis Semen, Imperatae Rhizoma, Hedyotis Diffusae Herba, and Tripterygii Radix were reported that they have good antioxidant activity and cholesterol-reducing activity (Wang et al 2019). Arachidonic acid (AA), a constituent of cell Fig.…”
Section: Discussionmentioning
confidence: 99%